An Estimate of the Formal Autonomy of the Telecommunications Regulator in Peru - Ruiz Díaz, Gonzalo Martín (2015)
This article talks about the concept of autonomy of regulatory agencies, implementing the methodology developed by Gilardi in order to estimate the formal autonomy of the Peruvian telecommunications regulator (OSIPTEL). The results allow to appreciate that the formal autonomy of OSIPTEL is slightly above the average of a set of pairs organisms levels suggesting that a formal level, the regulatory framework gives the Peruvian telecommunications regulator reasonable degree of autonomy compared to standards international. Also, the relation between the concept of formal autonomy and de facto autonomy is discussed, from developments of Maggeti Gilardi, specially the importance of broadening and supplementing the analysis of the first with the second, in order to obtain greater insight into the strengths and weaknesses of regulation in Peru and the region, and outline an agenda for strengthening.